Aplikasi Pemberian Pupuk NPK dan Pengaturan Air terhadap P-Tersedia, Serapan P dan Hasil Padi Sawah (Oryza Sativa L.) pada Inceptisols Asal Jatinangor - Asti Asfianti; Emma Trinurani S; Anni Yuniarti; Eso Solihin (Soilrens, 2016)
This research was conducted to find out the effect of application NPK compound and water regulation on soil phosphorus, P uptake and yield of rice (Oryza sativa L.) on Inceptisols. The study was conducted from in late May to October 2015. at the field station of soil and water management, Soil Science and Land Resources Department, Faculty of Agriculture, Padjadjaran University, Jatinangor, Sumedang. The experimental design used was Randomized Block Design (RBD) with ten treatments and three replications, consisted of : without treatment (control), waterlogged 5 cm; 150 kg Ha-1, waterlogged 5 cm; 300 kg Ha-1, waterlogged 5 cm; 450 kg Ha-1, waterlogged 5 cm; 600 kg Ha-1, waterlogged 5 cm; 750 kg Ha-1, waterlogged 5 cm; local recommended dosage, waterlogged 5 cm; 450 kg Ha-1, macak-macak; 450 kg Ha-1, intermittent 1 day, macak-macak; 450 kg Ha-1, intermittent 3 days, macak-macak. The results showed that there were effect of soil phosphorus, P uptake and yield of Rice on Inceptisol. Suppy NPK dose of 750 kg ha-1 were waterlogged 5 cm provides the highest content of available P amounted to 51.88 ppm P, P uptake of 0.93% and the highest yield of 9.24 kg.ha-1.